Do we need CBCTs for sufficient diagnostics?-dentist-related factors - Josipa Radic; Raphael Patcas; Bernd Stadlinger; Daniel Wiedemeier; Martin Rücker; Barbara Giacomelli-Hiestand (SpringerOpen, 2018)
Abstract Background The aim of this study was to assess the diagnostic accuracy of various dentoalveolar pathologies based on panoramic radiography (OPG), cone beam computed tomography (CBCT) and printed 3D models in consecutive order; and to evaluate the impact of specialisation of residents in oral surgery (OS) versus residents in orthodontics (ORTH). Methods Fourteen residents were recruited to evaluate nine selected cases with different dentoalveolar pathologies. The residents were given for each case an OPG, a CBCT and a printed 3D model. For each case and imaging modality, the residents were asked several questions relating to (i) diagnosis, and (ii) the request for consecutive imaging in order to enable treatment. Further, aspects like impact of specialisation (OS versus ORTH), gender and years of experience were analysed. Results In this study, diagnostic accuracy (i) improved for OS from OPG to CBCT (OPG 66.3%, CBCT 83.4%) and likewise for ORTH (OPG 63.7%, CBCT 78.0%). 3D models generally did not seem more useful than CBCTs. For treatment planning (ii), residents in orthodontics considered OPGs significantly more often as sufficient compared to residents in oral surgery (OR 6.3, p < 0.001). Further, the odds to request a CBCT after OPG for treatment planning is influenced by dentist-related factors: female dentists (OR 3.8) or residents with limited professional experience as dentists (OR 3.0) asked more frequently for a CBCT. Conclusions Overall diagnostic accuracy is decent with OPG and can be improved with CBCT. Specialisation seems to have a moderate impact on diagnostic accuracy, but influences whether a CBCT was requested for treatment planning. Based on these findings, future studies shall analyse the diagnostic accuracy of specific pathologies in higher number in order to substantiate the present findings with regard to specific pathologies.